2010
DOI: 10.1037/a0018799
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime suicidal ideation and suicide attempts in Asian Americans.

Abstract: Few studies have examined the role of culturally relevant factors in suicidal behavior among Asian Americans. Using the National Latino and Asian American Study (NLAAS) (Alegria et al., 2004;Heeringa et al., 2004), the current study examined the role of culturally related variables (family conflict, perceived discrimination, and ethnic identity) on suicidal ideation and suicide attempts in a nationally representative sample of 2,095 Asian Americans. Important covariates were sociodemographic characteristics (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
176
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(206 citation statements)
references
References 49 publications
22
176
7
1
Order By: Relevance
“…The suicide mortality per 100,000 persons in Korea increases with age from 4.5 deaths in those between the ages of 10 and 19 years to 78.6 deaths among those 80 years and over (1). Although a few studies have found no association between age and suicide attempts (8,11), many studies have reported that suicide attempts are predicted by a younger age (5,6,12,15). In this study, we found that suicide attempts were predicted by a younger age in both males and females, suggesting that younger age is a potent predictor of suicide attempts in both genders.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The suicide mortality per 100,000 persons in Korea increases with age from 4.5 deaths in those between the ages of 10 and 19 years to 78.6 deaths among those 80 years and over (1). Although a few studies have found no association between age and suicide attempts (8,11), many studies have reported that suicide attempts are predicted by a younger age (5,6,12,15). In this study, we found that suicide attempts were predicted by a younger age in both males and females, suggesting that younger age is a potent predictor of suicide attempts in both genders.…”
Section: Discussionsupporting
confidence: 61%
“…However, previous findings regarding the association between gender and suicide attempts have been inconsistent; some studies found that females have a greater risk for lifetime suicide attempts compared with males (5,6,8,10), while others found that gender was not associated with suicide attempts (7,(11)(12)(13)15). Until now, the association between gender and suicide attempts had not been determined in Korea, although gender was not significantly associated with suicide attempts in this study (data not shown).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…After evidence-based research from different Institutes provided the results indicating the benefits of mind-body intervention for some health issues (cardiovascular and neuromuscular conditions) [20][21][22][23][24][25][26], or psychological conditions (including depression) [27][28][29][30][31][32], investigators in one of them demonstrate in pilot studies that the RR-based group intervention, and other modalities (i.e., tai chi, Qigong, mindfulness training) have effect on treating mild and moderate depression symptoms [33][34][35] and maybe regarded as adjunctive treatment for other conditions. Their efforts also have been added into the processing of number increasing of studies [36][37][38] from different continents of the world showing the promise of multimodal mind-body group interventions for patients with depression.…”
Section: Relaxation Responsementioning
confidence: 99%
“…Esto hace pensar que la identidad étnica positiva podría actuar como un regulador importante en la no aparición de depresión e ideación suicida, especialmente en adolescentes, al encontrarse éstos mejor equipados para contrastar los efectos negativos del estrés aculturativo y la discriminación. 6 En el mismo sentido, los jóvenes de minorías con fuertes identidades étnicas relacionadas con su cultura de origen muestran una disminución en los casos de suicidio e ideación suicida; 7 por el contrario, hay evidencia de que el estrés provocado por el proceso de aculturación puede ser un factor de riesgo para la ideación suicida. 8 El estrés aculturativo puede incluir variables como la discriminación, la falta de comprensión del lenguaje, nivel socioeconómico bajo, conapoyo.…”
unclassified